Kingship in the Mycenaean world and its reflections in the oral tradition - Shear, Ione Mylonas, 1936- (Prehistory monographs, 2004)
During the last few decades, there has been great interest in the problems of defining the extent and nature of kingship in the Mycenaean world. Questions concerning the degree of economic and religious power held by the king have been given special emphasis. This book surveys the conclusions drawn by individual scholars studying the Linear B tablets, contrasts their theories with our knowledge of the Mycenaean kingdoms as derived from the archaeological record, and finally compares this evidence with possible reflections in the oral tradition, specifically in the Iliad and Odyssey . This appr.